2016
DOI: 10.1016/j.bbi.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial delivery of interleukin-17A via adeno-associated virus fails to induce physical and learning disabilities and neuroinflammation in mice but improves glucose metabolism through AKT signaling pathway

Abstract: Interleukin-17A (IL-17A) is generally considered as one of the pathogenic factors involved in multiple sclerosis (MS). Indirect evidence for this is that IL-17A-producing T helper 17 (Th17) cells preferentially accumulate in lesions of MS and experimental autoimmune encephalomyelitis (EAE). However, a direct involvement of IL-17A in MS pathogenesis is still an open question. In this study, we overexpressed IL-17A in the brains of mice (IL-17A-in-Brain mice) via recombinant adeno-associated virus serotype 5 (rA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 101 publications
(115 reference statements)
0
8
0
Order By: Relevance
“…The bioactivity of IL-17A produced by the AAV-IL-17A vector was confirmed using 3T3 cells described previously (Yang et al , 2016). To explore the potential role of IL-17A in AD, we intracranially delivered rAAV5-IL-17A into 2-month-old TgAPPswe/PS1dE9 mice.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…The bioactivity of IL-17A produced by the AAV-IL-17A vector was confirmed using 3T3 cells described previously (Yang et al , 2016). To explore the potential role of IL-17A in AD, we intracranially delivered rAAV5-IL-17A into 2-month-old TgAPPswe/PS1dE9 mice.…”
Section: Resultsmentioning
confidence: 93%
“…A rAAV vector, rAAV5-IL-17A, was prepared as described previously (Yang et al , 2016). A control rAAV vector encoding LacZ, rAAV5-LacZ, was similarly prepared.…”
Section: Methodsmentioning
confidence: 99%
“…The present results suggested the presence of an indirect mechanism during the expression of rate-limiting enzymes mediated by miR-218. Previous studies have indicated that Akt, JNK, ERK and NF-κB signaling pathways play important roles in glucose metabolism regulation (33)(34)(35)(36)(37)(38)(39)(40). Therefore, in the present study the phosphorylation of these proteins was detected in A549-GLUT1 cells after transfection with miR-218 mimics.…”
Section: Discussionmentioning
confidence: 67%
“…At the age of 11.5 months, the mice were conducted for the IPGTT and ITT, as previously described [ 30 , 31 ]. The animals ( n = 12/group) were fasted for 16 h, weighed, and intraperitoneally injected with D-glucose (1.5 g/kg) for the IPGTT.…”
Section: Methodsmentioning
confidence: 99%
“…Epididymal adipocytes were prepared as previously described [ 31 , 32 ]. In brief, adipose tissue ( n = 4/group) was digested at 37°C in PBS (without calcium and magnesium) containing 2% bovine serum albumin (BSA) and 2 mg/ml collagenase VI (Sigma, St. Louis, MO) for 45 min.…”
Section: Methodsmentioning
confidence: 99%